IMPACT OF NANO NPK FERTILIZERS TO CORRELATION BETWEEN PRODUCTIVITY, QUALITY AND FLAG LEAF OF SOME BREAD WHEAT VARIETIES - & AL-Hassan, Burhan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research was carried out at the fields of Field Crops Dept. Coll. of Agric. Univ. of Baghdad, during the season 2017-2018, to investigate the effect of Nano fertilizer NPK (Fn1, Fn2, Fn3: spraying with the liquid fertilizer 20%-9%-10% with 15% concentration of the levels 750:90:600, 500: 60: 400 and 250: 30: 200 mg L-1 and Fgn1, Fgn2, Fgn3: spraying the liquid fertilizer at 7.50% concentration of the same levels plus 50% of the soil Fertilizer) on flag leaf area, grain yield and some of the quality traits of three wheat varieties. Using randomized complete block design with split plot arrange with three replications. The results showed increases in grains yield (48.99%), protein percentage (27.24%), gluten ratio in flour (58.45%) and flag leaf area (38.69%), its dry weight (41.89%) , total chlorophyll content (18.33%), nitrogen (19.37%), phosphorus (44.11%) and potassium (12.03%) when fertilized with Fn1 treatment compared with the control treatment (Fg: soil Fertilizer 184 N, 39.56 P, 41.50 K kg ha-1). The Fgn1 and Fgn2 treatments gave increase in the specific weight of flag leaf at 31.38  and 11.44% respectively, also the Fgn1 and Fgn2 treatments increase in grain carbohydrate content at 15.00 and 10.55 % respectively compared with Fg treatment. Arrangement of the Fertilizers  treatments in their general progressively positive effects on growth, yield and quality parameters was Fn1>Fgn1>Fn2>Fgn2> Fn3>Fgn3>Fg. The Bhoth-158 variety gave the highest grains yield (5.25 tons ha-1) with increase ratios 13.14 and 23.82% compared with Uruq and IPA-99 varieties. The IPA-99 was superior in its flour content of highest ratio of the dry gluten (16.99%). The Bhoth-158 variety showed positive response to Nano Fertilizers  treatments especially the Fn1 treatment followed by IPA-99 variety. There was highly significant correlation between total grains yield and each of the flag leaf area, its dry weight and chlorophyll content, its time staying active and content of nitrogen, phosphorus and potassium.